Study of the effect of synthesized high voltage electric charge of a powder mixture on the physical and mechanical properties of epoxy composites for the transport industry - Buketov А.V.; Syzonenko O.М.; Bezbakh О.М.; Torpakov , A.S.; Lypian , Ye.V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
For the formation of composite materials and protective coatings for the transport industry, ED-20 epoxy yanoic oligomer, the polyethylene polyamine PEPA and microfine fractions of high-voltage synthesized powder charge were used. The dependence of the content of microdispersed powder on the adhesive, physical and mechanical properties, and residual stresses of epoxy composites has been investigated. It has been proved that for the formation of a composite material or protective coating with improved adhesive and cohesive properties, the optimal particle content is 0.05–0.50 parts by weight per 100 parts by weight of the ED-20 epoxy oligomer. Such materials are characterized by increased mechanical strength and the ability to resist static and dynamic loads, since their properties are significantly increased compared with the matrix. The obtained results of experimental studies of physical and mechanical properties of composite materials are consistent with the test results of samples with adhesive characteristics, indicating their reliability.